USE OF TECHNOLOGY FOR SKILL DEVELOPMENT IN HOMEMAKING - Kaur, Manmeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of technology in homemaking has revolutionized the way households are managed. From online platforms offering tutorials to smart home devices streamlining daily tasks, technology empowers individuals to develop and enhance their homemaking skills. This paper explores the extensive range of technological tools and resources available for skill development in homemaking, their impact on efficiency, creativity, and sustainability, and the challenges and opportunities associated with their adoption in diverse socio-economic contexts.